The suggested tasks for Master’s graduates in reproductive health by experts in Iran - Shakour, Mahsa (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Reproductive health is an important health topic. There are many challenges in reproductive health and it is necessary to train experts to manage them. The aim of this study was to define the tasks of Master of Science (MSc) graduates in reproductive health through comprehensive needs assessment to establish the course. MATERIALS AND METHODS: The study comprised of three steps. In the first step, through literature review, the draft and basic fields of main tasks were defined. In the second step, by establishing a focus group of 10 experts, the tasks were extracted on the basis of the country’s needs. In the third step, a Delphi study was carried out among 51 experts who were selected to finalize the list of tasks and their priorities using three criteria of “importance”, “feasibility” and “availability”. FINDINGS: 57 tasks were extracted with regard to the four main functions of management and planning, education, consultation, and screening in reproduction age of men and women. According to Delphi’s results and their priorities, 45 tasks were important and feasible but not available, and they were higher-priority tasks. CONCLUSIONS: The tasks extracted are consistent with the framework of reproductive health provided by the World Health Organization (WHO) and the American Guideline of Educational Planning. However, considering the differences of problems in Iran comparing with other countries, the list is not exactly similar to any list prepared for other countries. Therefore, it is necessary to consider the results of this research in university curriculums.